Inequalities in infant mortality rate in India from 1999-2020 - Tripathy, Satya S.; Behera, Priyanka; Pradhan, Subrat K.; Mishra, Sanjeeb K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Infant Mortality Rate is a key indicator of child survival and overall health system performance. Gender inequality in IMR, particularly in low and middle-income countries like India, reflects broader disparities in access to health care and societal preferences. The aim of this study is to assess the magnitude and trends of gender inequalities in infant mortality in India from 1999 to 2020. Methods: This study utilized data from DHS and other related surveys, analysed through the WHO’s health equity assessment toolkit (HEAT). IMR was disaggregated by gender and other equity stratifies (economic status, maternal age, place of residence and education). Inequality was assessed using simple (difference, ratio) and complex (population attributable risk [PAR], population attributable fraction [PAF]) measures. Results: IMR remained consistently higher among males compared to females. However, the PAR and PAF values for gender inequality were consistently zero. Disparities were found across economic, educational, and residential dimensions. The poorest households, rural populations, mothers with no education, and younger mothers (15-19 years) exhibited higher IMR. Over time, these inequalities have declined but still remain significant, especially in wealth and education dimensions. Conclusions: India has seen a decline in infant mortality over the past two decades, persistent inequalities - particularly along socio-economic and educational lines continue to challenge equity in child survival. Addressing these disparities requires targeted public health interventions and socio-economic reforms. The use of both simple and complex inequality metrics provides valuable insight for policymakers in prioritizing efforts towards more equitable health outcomes.